2018
DOI: 10.1038/s41467-018-04330-5
|View full text |Cite
|
Sign up to set email alerts
|

Coherent X-rays reveal the influence of cage effects on ultrafast water dynamics

Abstract: The dynamics of liquid water feature a variety of time scales, ranging from extremely fast ballistic-like thermal motion, to slower molecular diffusion and hydrogen-bond rearrangements. Here, we utilize coherent X-ray pulses to investigate the sub-100 fs equilibrium dynamics of water from ambient conditions down to supercooled temperatures. This novel approach utilizes the inherent capability of X-ray speckle visibility spectroscopy to measure equilibrium intermolecular dynamics with lengthscale selectivity, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 71 publications
(105 reference statements)
6
52
0
Order By: Relevance
“…In our previous studies 42,50 , we measured a typical photon flux of 0.03 photons/pixel/pulse from gold nanopowder at q = 2.6 Å −1 . Subsequent studies have shown that it is still possible to obtain meaningful speckle contrast from such low intensity speckle, as it was demonstrated for scattering signals from amorphous solids and liquids using coherent x-rays after Si(111) monochromator 49,52 . While the narrower energy bandwidth of Si(422) reflection used in the split-and-delay helps to improve the longitudinal coherence, it decreases the photon flux considerably.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…In our previous studies 42,50 , we measured a typical photon flux of 0.03 photons/pixel/pulse from gold nanopowder at q = 2.6 Å −1 . Subsequent studies have shown that it is still possible to obtain meaningful speckle contrast from such low intensity speckle, as it was demonstrated for scattering signals from amorphous solids and liquids using coherent x-rays after Si(111) monochromator 49,52 . While the narrower energy bandwidth of Si(422) reflection used in the split-and-delay helps to improve the longitudinal coherence, it decreases the photon flux considerably.…”
Section: Discussionmentioning
confidence: 94%
“…However, thanks to high energy resolution provided by delay line optics the speckle contrast will increase at high scattering angles. For instance at q = 1.95 Å −1 the expected contrast is 2.2 times higher compared www.nature.com/scientificreports www.nature.com/scientificreports/ to Si(111) optics used in 52 . Blue triangle in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The scope of XPCS will be significantly enlarged with the availability of extremely brilliant synchrotron sources and even faster pixel array detectors. The feasibility of studying ultrafast dynamics using an alternative method-speckle visibility spectroscopy-has already been demonstrated at the X-ray free-electron laser (XFEL) [117]. However, this method has limitations when studying complex relaxation processes involving non-exponential g 2 (q, t) and non-monotonic q dependence.…”
Section: Equilibrium Dynamicsmentioning
confidence: 99%